Mechanical Wiping Increases the Efficacy of Liquid Disinfectants on SARS-CoV-2 - Sloan, Angela; Kasloff, Samantha B.; Cutts, Todd (Frontiers in Microbiology, 2022)
High-touch environmental surfaces are acknowledged as potential sources of pathogen transmission, particularly in health care settings where infectious agents may be readily abundant. Methods of disinfecting these surfaces often include direct application of a chemical disinfectant or simply wiping the surface with a disinfectant pre-soaked wipe (DPW). In this study, we examine the ability of four disinfectants, ethanol (EtOH), sodium hypochlorite (NaOCl), chlorine dioxide (ClO2), and potassium monopersulfate (KMPS), to inactivate SARS-CoV-2 on a hard, non-porous surface, assessing the effects of concentration and contact time. The efficacy of DPWs to decontaminate carriers spiked with SARS-CoV-2, as well as the transferability of the virus from used DPWs to clean surfaces, is also assessed. Stainless steel carriers inoculated with approximately 6 logs of SARS-CoV-2 prepared in a soil load were disinfected within 5 min through exposure to 66.5% EtOH, 0.5% NaOCl, and 1% KMPS. The addition of mechanical wiping using DPWs impregnated with these biocides rendered the virus inactive almost immediately, with no viral transfer from the used DPW to adjacent surfaces. Carriers treated with 100 ppm of ClO2 showed a significant amount of viable virus remaining after 10 min of biocide exposure, while the virus was only completely inactivated after 10 min of treatment with 500 ppm of ClO2. Wiping SARS-CoV-2-spiked carriers with DPWs containing either concentration of ClO2 for 5 s left significant amounts of viable virus on the carriers. Furthermore, higher titers of infectious virus retained on the ClO2-infused DPWs were transferred to uninoculated carriers immediately after wiping. Overall, 66.5% EtOH, 0.5% NaOCl, and 1% KMPS appear to be highly effective biocidal agents against SARS-CoV-2, while ClO2 formulations are much less efficacious.